Vancomycin in ICU Patients with Gram-Positive Infections: Initial Trough Levels and Mortality - Alshehri N (Dove Medical Press, 2020)
Nadiyah Alshehri,1,2 Anwar E Ahmed,3 Nagarajkumar Yenugadhati,2,4 Sundas Javad,2,4 Khalid Al Sulaiman,1 Hasan M Al-Dorzi,5 Majed Aljerasiy,4 Motasim Badri2,4 1Pharmaceutical Care Department, Ministry of National Guard- Health Affairs, Riyadh, Saudi Arabia; 2Department of Epidemiology & Biostatistics, College of Public Health and Health Informatics, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 3Henry M. Jackson Foundation for the Advancement of Military Medicine, Bethesda, MD, USA; 4King Abdullah International Medical Research Center, King Saud Bin-Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 5Intensive Care Department, College of Medicine King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi ArabiaCorrespondence: Nadiyah AlshehriDepartment of Epidemiology & Biostatistics, College of Public Health and Health Informatics, King Saud bin Abdulaziz University for Health Sciences, P.O. Box: 47323, Riyadh 11552, Saudi ArabiaEmail alshehrina2@ngha.med.saBackground: Vancomycin is one of the most common therapeutic agents for treating gram-positive infections, particularly in critically ill patients. The aim of this study was to identify factors associated with initial therapeutic vancomycin trough levels and mortality in a tertiary-care intensive care unit (ICU).Methods: This retrospective study evaluated 301 adult ICU patients admitted to King Abdulaziz Medical City in Riyadh between October 1, 2017 and December 31, 2018 with confirmed gram-positive infections and received intravenous vancomycin. Vancomycin trough levels of 15– 20 mg/L for severe infections and 10– 15 mg/L for less severe infections were considered therapeutic.Results: The patients were relatively older with a mean age of 60 (SD ± 20) years. Initial vancomycin trough levels were therapeutic in 168 (55.8%). Factors associated with initial therapeutic vancomycin trough levels were female gender (adjusted odds ratio [aOR]=2.575), older age (aOR=1.024), receiving a loading dose (aOR=2.445), having bacteremia (aOR=2.061), and high platelet count (aOR=1.003). On the other hand, the increase of estimated glomerular filtration rate (eGFR) (aOR=0.993) and albumin levels (aOR=0.944) were associated with lower odds of initial therapeutic vancomycin trough levels. Factors associated with higher mortality were female gender (adjusted hazard ratio [aHR]=2.630), increased body weight (aHR=1.021), cancer (aHR=3.451), and high APACHE II score (aHR=1.068).Conclusion: The study identified several factors associated with achieving initial therapeutic vancomycin trough levels (i.e. older age, female gender, receiving a loading dose, bacteremia, high platelets count, low eGFR and albumin level). These factors should be considered in the dosing of vancomycin in critically ill patients with gram-positive infections.Keywords: vancomycin dosage, pharmacokinetics, renal function, serum trough levels, mortality